The Ratio of Added Value to Marginal Land Use of Embankments in Wisata Agribisnis - Hartati, Hartati; Nuryadi, Ahmad Muhlis; Rosmalah, Sitti (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
The main activity of pond land in Wisata Agribisnis is the cultivation of milkfish. However, to maximize the use of pond land, pond farmers plant dragon fruit plants to add value to land management. The aim of this research is to analyze the value-added ratio on marginal land. This research method is a case study of marginal land use in agribusiness tourism, with qualitative and quantitative data. Quantitative data are analyzed with income analysis and value-added analysis. Qualitative data describe the marginal land use of embankments. The research results of dragon fruit planting in the marginal areas of pond embankments showed: 1) dragon fruit plants do not pollute pond water, this is because the structure of dragon fruit plants is similar to cactus plants, 2) full sunlight in ponds is very suitable for dragon fruit plants, 3) plants dragon fruit is very tolerant of brackish water, 4) the taste of dragon fruit remains sweet in root conditions close to brackish water, 5) dragon fruit plants continue to bear fruit even though planted in marginal land at the embankments of the pond. The results of the research on marginal land use of pond embankments by planting dragon fruit plants added value of Rp. 17,302,857, with a ratio of 85%. Pond farmers can take advantage of the marginal land of their ponds by planting dragon fruit plants.